2006
DOI: 10.1021/jp057182+
|View full text |Cite
|
Sign up to set email alerts
|

Atom and Ion Chemistry in Low Pressure Hydrogen DC Plasmas

Abstract: The chemical composition of a low-pressure hydrogen dc plasma produced in a hollow cathode discharge has been measured and modeled. The concentrations of H atoms and of H + , H 2 + and H 3 + ions were determined with a combination of optical spectroscopic and mass spectrometric techniques, over the range of pressures (p ∼0.008-0.2 mbar) investigated. The results were rationalized with the help of a zero-order kinetic model. A comparatively high fraction (∼0.1 ( 0.05) of H atoms, indicative of a relatively smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
135
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 120 publications
(150 citation statements)
references
References 49 publications
(91 reference statements)
13
135
0
2
Order By: Relevance
“…In a previous study of pure H 2 plasmas in the same reactor, emission spectroscopy measurements in conjunction with a collisional radiative model [33] showed that the H 2 vibrational populations in our plasmas are concentrated in the lowest levels and can be roughly described by a vibrational temperature of ~ 3000 K. For this vibrational temperature, the population of H 2 (v≥1) is ~ 12%. Given the high threshold for electron impact dissociation of H 2 (~ 11 eV) as compared with the first vibrational quantum of H 2 (~ 0.5 eV), we do not expect a significant contribution of vibrationally excited molecules, H 2 (v), to the global electron impact dissociation of H 2 .…”
Section: Modelmentioning
confidence: 57%
See 4 more Smart Citations
“…In a previous study of pure H 2 plasmas in the same reactor, emission spectroscopy measurements in conjunction with a collisional radiative model [33] showed that the H 2 vibrational populations in our plasmas are concentrated in the lowest levels and can be roughly described by a vibrational temperature of ~ 3000 K. For this vibrational temperature, the population of H 2 (v≥1) is ~ 12%. Given the high threshold for electron impact dissociation of H 2 (~ 11 eV) as compared with the first vibrational quantum of H 2 (~ 0.5 eV), we do not expect a significant contribution of vibrationally excited molecules, H 2 (v), to the global electron impact dissociation of H 2 .…”
Section: Modelmentioning
confidence: 57%
“…The DC plasma reactor used for the experiments has been described in previous works [33,34]. It consists of a stainless steel grounded hollow cathode reactor (34 cm length, 10 cm diameter) with a central anode.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations